Transactions on computational collective intelligence III - Nguyen, Ngoc Thanh; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
These Transactions publish research in computer-based methods of computational collective intelligence (CCI) and their applications in a wide range of fields such as the Semantic Web, social networks and multi-agent systems. TCCI strives to cover new methodological, theoretical and practical aspects of CCI understood as the form of intelligence that emerges from the collaboration and competition of many individuals (artificial and/or natural). The application of multiple computational intelligence technologies such as fuzzy systems, evolutionary computation, neural systems, consensus theory, etc., aims to support human and other collective intelligence and to create new forms of CCI in natural and/or artificial systems. This third issue contains a collection of 10 articles selected from high-quality submissions addressing advances in the foundations and applications of computational collective intelligence.
Electronic reproduction.
Keywords: Electronic books; Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Information systems; Artificial intelligence